Democracy - Connolly, Sean J. (Systems of government, 2017)
Democracy reveals the inner working of this type of government, setting it in the context of history and relating it to today's current affairs. Readers will learn how a democracy functions internally and within the wider world community. They will also encounter some of the dilemmas, contradictions and compromises that seem to be an essential part of even the most idealistic political systems. Part of the Systems of Government series, these books feature fact boxes, timelines and carefully chosen images that complement informative text that is packed with case studies and first-hand accounts. Voting Booth panels invite readers to consider thorny issues, both historical and current, and to form their own opinions. Ages 13+